La simulación frente a prácticas docentes tradicionales en la adquisición de competencias clínicas en reanimación cardiopulmonar en estudiantes de medi-cina de la Universidad Técnica Particular de Loja durante el período septiembre 2012 - febrero 2013 - Rodríguez Ponce, Marcelo David (2014)
The present study aims to assess the acquisition of clinical skills in cardiopulmonary resuscita-tion (CPR) by medical students, for which the objective structured clinical evaluation (OSCE) format has been used, applied to two groups: the first one consisting of 74 third-semester stu-dents, who attended a workshop on cardiopulmonary resuscitation based on simulation methods (intervention group); and the second one comprised of 75 seventh-semester students, who re-ceived training on the same topic through traditional teaching methods (control group). The level of acquisition of clinical competence was measured in both groups by using an Objective Struc-tured, Clinical Evaluation (OSCE), in order to make an analysis of student performance. It was demonstrated that the group trained by traditional teaching methods did not reach an adequate level of competence, as it was categorized as “insufficient” and “deficient”. In the other hand, from the group undergoing simulation-based teaching, the majority reached a category of “nota-ble” in the acquisition of clinical skills